Green Harmony: Granular Fertilizer and Liquid Soap from Eco Enzymes for The "Sustainable Elderly" Mission - Putranti, Honorata Ratnawati Dwi; Swastuti, Endang; Warsono, Albertus Kristiyo (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
In some communities, the elderly are often seen as a burden rather than valuable assets. This view not only diminishes their intrinsic value within families and society but also overlooks their potential to make significant contributions. This community service focuses on the importance of integrating the elderly into productive activities that not only improve their health and psychological well-being but also reduce the social and economic burden on the younger generation. Through involvement in environmentally friendly product manufacturing projects such as granular fertilizer and liquid soap made from eco-enzymes, the elderly are given the opportunity to participate in meaningful efforts and become agents of change that support environmental sustainability. This service utilizes a participative approach, emphasizing the active involvement of the community at RW 7, Ngesrep Sub-district, Banyumanik District, Semarang, especially the elderly group (55-75 years), in all stages of activity, from planning to implementation and evaluation. It also involves students as a manifestation of the Institutional Key Performance Indicators (IKU) with indicators of student activities outside the campus. The exploration of these activities is expected to change the public's perception of the elderly, portraying the elderly group as a transformative resource. The introduction of environmentally friendly technology, involving them in production, is expected to enhance environmental sustainability and maximize the welfare of the elderly (Sustainable Elderly). The conclusion of this service underscores the urgency to change policies and social practices to include the elderly more inclusively in all aspects of community life. The implications of these findings lead to policy recommendations that are more focused on the integration and empowerment of the elderly, particularly at RW 7, and the introduction of eco-enzyme product diversification, namely granular fertilizer and liquid soap.